The ATLAS3D project – XXVII. Cold gas and the colours and ages of early-type galaxies. Issue 4 (16th September 2014) - Young, Lisa M.; Scott, Nicholas; Serra, Paolo; Alatalo, Katherine; Bayet, Estelle; Blitz, Leo; Bois, Maxime; Bournaud, Frédéric; Bureau, Martin; Crocker, Alison F.; Cappellari, Michele; Davies, Roger L.; et al.
Abstract : We present a study of the cold gas contents of the Atlas 3D early-type galaxies, in the context of their optical colours, near-ultraviolet colours and Hβ absorption line strengths. Early-type (elliptical and lenticular) galaxies are not as gas poor as previously thought, and at least 40 per cent of local early-type galaxies are now known to contain molecular and/or atomic gas. This cold gas offers the opportunity to study recent galaxy evolution through the processes of cold gas acquisition, consumption (star formation) and removal. Molecular and atomic gas detection rates range from 10 to 34 per cent in red sequence early-type galaxies, depending on how the red sequence is defined, and from 50 to 70 per cent in blue early-type galaxies. Notably, massive red sequence early-type galaxies (stellar masses >5 × 10 10 M⊙, derived from dynamical models) are found to have H i masses up to M (H i )/ M * ∼ 0.06 and H2 masses up to M (H2 )/ M * ∼ 0.01. Some 20 per cent of all massive early-type galaxies may have retained atomic and/or molecular gas through their transition to the red sequence. However, kinematic and metallicity signatures of external gas accretion (either from satellite galaxies or the intergalactic medium) are also common, particularly at stellar masses ≤5 × 10 10 M⊙, where such signatures are found in ∼50 per cent of H2 -rich early-type galaxies. Our data are thus consistent with a scenario in which fast rotator early-type galaxies are quenched former spiral galaxies which have undergone some bulge growth processes, and in addition, some of them also experience cold gas accretion which can initiate a period of modest star formation activity. We discuss implications for the interpretation of colour–magnitude diagrams.